DIETARY APPROACHES TO ENHANCE DRUG DELIVERY SYSTEMS: A FOCUS ON NANOENCAPSULATION TECHNIQUES (International Journal of Food and Nutritional Sciences, 2022)
Nanoencapsulation techniques have emerged as a promising strategy to enhance the bioavailability and efficacy of drug delivery systems. This approach involves the use of nanoscale carriers to protect and deliver active pharmaceutical ingredients (APIs) to specific sites within the body, thereby improving therapeutic outcomes. One innovative avenue to optimize these drug delivery systems is through dietary interventions that complement nanoencapsulation. By incorporating bioactive compounds from natural foods, such as polyphenols, lipids, and proteins, into the nano-carriers, the stability, solubility, and permeability of the encapsulated drugs can be significantly enhanced. These dietary components can act as co-delivery agents, facilitating the targeted release of drugs and enhancing their absorption in the gastrointestinal tract. Moreover, dietary approaches can mitigate the adverse effects often associated with conventional drug delivery methods by promoting a more controlled and sustained release of APIs. The integration of dietary strategies with nanoencapsulation not only offers a means to enhance drug delivery but also aligns with the growing interest in personalized medicine, where dietary habits can be tailored to improve individual responses to drug therapies. This review explores the synergistic potential of dietary components in nanoencapsulation, providing insights into the design and optimization of next-generation drug delivery systems that are more efficient, safe, and patient-centric. The discussion highlights recent advances in the field, challenges faced, and future directions for research, emphasizing the role of nutrition in advancing the efficacy of nanoencapsulation techniques in drug delivery.